2020
DOI: 10.1248/cpb.c20-00524
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Pretreatment Attenuates Anoxia-Reoxygenation Induced Injury in Cardiac Myocytes <i>via</i> a BRCA1 Dependent Pathway

Abstract: Breast cancer type 1 sensitive protein (BRCA1) is a well-known tumor suppressor and its role in oxidative stress has been confirmed. The purpose of this study is to evaluate whether paeonol has a protective effect on myocardial hypoxia-reoxygenation (A/R) injury, and to explore H9C2 cells through a mechanismdependent pathway mediated by BRCA1. H9C2 cells were pretreated with paeonol (10 µM) for 18 h before hypoxia was induced to establish a cell model of myocardial ischemia/reperfusion (I/R) injury. Use commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…After that, the total RNA underwent reverse transcription and quantification on a Real-Time PCR system (7500, ThermoFisher, USA) using the One-Step SYBR Green qRT-PCR Kit (BL643B, Biosharp, China). Under the adoption of the 2 − ΔΔ CT method, B-type natriuretic peptide (BNP), atrial natriuretic peptide (ANP), major histocompatibility complex-B (B-MHC), GSK3A, CD36, PDK4 (Pyruvate dehydrogenase kinase 4), and Cpt1b (carnitine palmitoyltransferase 1B) expressions were normalized to glyceraldehyde-3-phosphate dehydrogenase (GAPDH) [ 12 ]. Supplementary Table 3 lists the primer sequences.…”
Section: Methodsmentioning
confidence: 99%
“…After that, the total RNA underwent reverse transcription and quantification on a Real-Time PCR system (7500, ThermoFisher, USA) using the One-Step SYBR Green qRT-PCR Kit (BL643B, Biosharp, China). Under the adoption of the 2 − ΔΔ CT method, B-type natriuretic peptide (BNP), atrial natriuretic peptide (ANP), major histocompatibility complex-B (B-MHC), GSK3A, CD36, PDK4 (Pyruvate dehydrogenase kinase 4), and Cpt1b (carnitine palmitoyltransferase 1B) expressions were normalized to glyceraldehyde-3-phosphate dehydrogenase (GAPDH) [ 12 ]. Supplementary Table 3 lists the primer sequences.…”
Section: Methodsmentioning
confidence: 99%
“…NF-κB interacts with the nucleus by regulating more than 200 genes, among which some produce inflammatory cytokines, which ultimately lead to excessive inflammation. H9C2 cells, which are damaged by hypoxia through BRCA1/ROS-regulated NLRP3 inflammasome/IL-1β and NF-κB/TNF-α/IL-6 pathways, can be improved by Paeonol ( 44 ). When intercellular macromolecular proteins aggregate, they are called inflammasomes, which promote the maturation of inflammatory cytokines ( 45 ).…”
Section: The Mechanism Of Myocardial I/r Injurymentioning
confidence: 99%
“…Pretreating with paeonol can significantly improve the hypoxia-reoxygenation (H/R) damage and the BRCA1 expression of H9C2 cells through the BRCA1/ROS-regulated NLRP3 inflammasome/IL-1β and NF-κB/TNF-α/IL-6 pathways. It may be a candidate drug for treating myocardial I/R injury ( 44 ).…”
Section: Cardioprotective Phytochemicals Attenuating Myocardial I/r I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Paeonol has currently been proven to have a cardioprotective effect on epirubicin-induced heart injury ( 18 ). Additionally, recent studies further demonstrated that paeonol pretreatment attenuates hypoxia-reoxygenation-induced injury of cardiomyocytes via the breast cancer type 1 sensitive protein (BRCA1)-dependent pathway, and paeonol attenuates transverse aortic constriction-induced HF through the ERK1/2 signaling pathway ( 19 , 20 ). Also, paeonol suppresses vasculogenesis via regulating vascular smooth muscle phenotypic switching, and it promotes Opa1-mediated mitochondrial fusion by activating the CK2α-Stat3 pathway in diabetic cardiomyopathy ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%